A study on public's acceptance towards herbal products marketed by Konsortium Pasifik Sama Sdn. Bhd. / Reynold Paul - Paul, Reynold (2006)
For this Project Paper, MKT660, I decide to make a study on the public's acceptance towards herbal products that being marketed by Konsortium Pasifik Sama Sdn. Bhd. KPS Sdn. Bhd. is a local company wholly owned subsidiary of Institute for Development Studies (Sabah) that focusing on commercializing their herbal product that uses from the natural resources within Sabah. From the KPS sales performance for the last five years (see Appendix 2), it show a decline in their sales performance. Thus, this research objective is to identify if the KPS herbal products are well accepted, to identify if there any other problem faces, to analyze whether the KPS current marketing approaches used are effective and lastly to identify the right marketing strategies that can be adopted by KPS in order to improve it's market position. The significant of this study will give a good impact firstly to the KPS Sdn. Bhd. then to the publics and lastly to the researcher as well. Two types of data collection method are used. They are primary data and secondary data. Primary data collection is conducted with distributing questionnaires, personal interviews and fields interviews. Secondary data are information which is already in existences such as journals, magazine, published documents, internet and so on. The sampling design process will consist of target population where the target population for this study will be defined. Then, the sampling frame will be used as the guidelines for identifying the target populations. The sampling technique used called the convenience sampling and the sampling size will be 120 respondents that will divided into four categories. The findings from the research will be conducted by using Statistic Package for Social Science program version 12.0 (SPSS v12.0) to analyze the data from the questionnaires given to the respondents.